(untitled) (Nexus International Journal of Science and Education, 2024)
This study explores the insights gained from a colloquium of secondary school teachers on multicultural education in classrooms. The colloquium provided a platform for teachers to engage in collaborative discussions and share their experiences, challenges, and effective practices related to implementing multicultural education. The target population for this study will be the twelve (12) participants from the line-up of public high school faculty, a junior high school unit who are still teaching during the school year 2022-2023. Through qualitative analysis of the colloquium proceedings, this study examines the key themes that emerged, including addressing challenges, addressing intersectionality, addressing diversity, educational equity, teacher preparation, enhancing learning outcomes, culturally responsive teaching, culturally responsive teaching, teacher professional development. The findings of the study disclosed the culturally responsive pedagogy, teacher professional development, and community engagement in fostering a culturally inclusive and equitable learning environment. The study contributes to the existing literature by providing insights from the perspectives of secondary school teachers, thus informing educators, policymakers, and researchers about the essential elements necessary for successful multicultural education implementation. The findings from this colloquium serve as a valuable resource for educational stakeholders aiming to enhance diversity, equity, and inclusion within the educational system.